2000
DOI: 10.3168/jds.s0022-0302(00)74878-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Bovine Milk Somatic Cell Count and Polymorphonuclear Leukocyte Level for Samples of Bulk Milk and Milk from Individual Cows

Abstract: The influence of various factors on the concentrations of polymorphonuclear neutrophilic leukocytes (PMN) in milk samples from bulk tanks and individual cows was investigated. While somatic cell counts (SCC) and PMN level were in both cases significantly correlated, lower correlation coefficients were found between SCC and PMN for samples of bulk tank milks than for milk samples from individual cows. Furthermore, plots of PMN concentrations versus SCC showed great variability in PMN in milk samples of similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 17 publications
6
48
0
6
Order By: Relevance
“…In the present study, the decrease in milk yield and milk lactose rates were observed when SCC increased and these findings were in accordance with previous reports (Kelly et al, 2000;Fernandes et al, 2004;Bansal et al, 2005). However, it was determined that the milk fat rate was increased.…”
Section: Correlation Between Somatic Cell Count and Milk Compositionsupporting
confidence: 82%
“…In the present study, the decrease in milk yield and milk lactose rates were observed when SCC increased and these findings were in accordance with previous reports (Kelly et al, 2000;Fernandes et al, 2004;Bansal et al, 2005). However, it was determined that the milk fat rate was increased.…”
Section: Correlation Between Somatic Cell Count and Milk Compositionsupporting
confidence: 82%
“…Given the variability in inflammatory responses between all cows that make up a herd. An average bulk milk SCC of 50 000 cells/mL is therefore not a realistic goal [23,33]. Prevalence of infection increases with mean bulk milk SCC but this is not tight relationship due to the lognormal nature of cow SCC.…”
Section: Somatic Cell Count Patterns At Herd Levelmentioning
confidence: 99%
“…Recently, Cooney et al [15] have suggested the direct role of the proteases (particularly cathepsin D) of the polymorphonuclear leukocytes on the ripening of Swiss-type cheese and on the high level of indigenous proteolysis in milk with high SCC and high PMN content. For Kelly et al [33], it would be of great interest to link change in PMN concentration, and not just SCC, to milk quality or processing characteristics of milk, indeed PMN have different enzyme profiles than macrophages. For these authors, the possibility exists that PMN may act as a marker for certain functional properties of milk, which could be used by processors to screen bulk milks.…”
Section: The Relationship Between Scc and Cheese Yield (Tab Iii)mentioning
confidence: 99%